2017
DOI: 10.1149/2.0651712jes
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Carbon@Co Nanocages/Nafion/Poly Tiopronin Composite Film and Its Application for Determination of Acetaminophen

Abstract: The carbon@Co nanocages/nafion/poly tiopronin composite film modified glassy carbon electrode (GCE) was prepared for the first time. The poly tiopronin was constructed by electropolymerization of tiopronin on the surface of GCE and the carbon@Co nanocages fabricated by the calcination of Co-based MOF (ZIF-67) under Ar atmosphere. The structure and surface morphology of the prepared carbon@Co nanocages were characterized using X-ray diffraction, scanning and transmission electron microscopy. The electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…25,26 Electrochemical techniques have been the most widely used because of advantages such as short response time, low consumption of samples and high sensitivity. [27][28][29][30][31] Electrospinning is a way to produce nanoparticles and microfibers from a homogeneous polymer solution. Nano-fibers are used because of advantages such as high porosity, high surface area and high stability.…”
mentioning
confidence: 99%
“…25,26 Electrochemical techniques have been the most widely used because of advantages such as short response time, low consumption of samples and high sensitivity. [27][28][29][30][31] Electrospinning is a way to produce nanoparticles and microfibers from a homogeneous polymer solution. Nano-fibers are used because of advantages such as high porosity, high surface area and high stability.…”
mentioning
confidence: 99%
“…However, many researches revealed that it could lead to serious hepatotoxicity and acute liver failure (ALF) with overdose. [4][5][6] For adults, the dosing of acetaminophen by mouth should be no more than 2g every day, and for children, the dosing should be reduced according to weight. Therefore, the assay of acetaminophen with high sensitivity and selectivity is highly required, and simple methodologies is also significant for the study of its metabolism and determination its content in biological fluids.…”
mentioning
confidence: 99%
“…Thanks to its superiorities of high sensitivity, fast response, rapid detection process and low operating cost as compared with other technologies, 5 electrochemical tool has been regarded as promising. Various materials including functionalized carbon materials, 6,7 nanocarbons-loaded metal nanoparticles, 4,8,9 metal oxide 10 or gold composites 11 have been intensively applied in the analysis of AC. Unfortunately, these modified electrodes 3,7,11 are less sensitive owing to their weak conductivity or poor contact during processing.…”
mentioning
confidence: 99%
“…In particular, the as-constructed sensor gives rise to an ultra-high sensitivity (102.05 μA μM −1 cm −2 ) and record-low detection limit (3.0 nM) for AC sensing among previously reported sensors. 2,4,6,7,[9][10][11][30][31][32] And it also manifests higher sensitivity for AC even in the presence of ascorbic acid (AA) and dopamine (DA), indicating its excellent selectivity. Simultaneously, the values determined in pharmaceutical sample with NWNC/GCE are highly coincident with the AC standard curve.…”
mentioning
confidence: 99%